An Analysis of Students’ Lack of Interest in Learning English at VII Grade Students in SMPS IT Darul Ihsan - Yuli Margawardani, Baiq; Udin, Udin; Lail, Husnul; Wayan Mira Susanti, Ni (Mataram University, 2024)
This study analyzes the factors contributing to seventh-grade students' lack of interest in learning English at SMPS IT Balik Batang. The objective is to identify and evaluate internal and external factors affecting students' motivation and engagement. This is the kind of mixed method research. The data were collected through questionnaires and interviews with 37 students, examining aspects such as physical conditions, psychological readiness, family support, and classroom environment. The results of the internal factor indicate that 89.19% of students found English difficult to understand due to issues such as pronunciation challenges and unclear explanations from teachers. Furthermore, in the external factors, 86.48% of students reported that distractions from peers significantly impacted their ability to focus during lessons. The study concludes that addressing these factors through improved teaching methodologies and effective classroom management can enhance students' interest and performance in learning English. It emphasizes the importance of tailored educational strategies to meet the specific needs of students.